L`épaule du lanceur : quel équilibre musculaire pour une meilleure performance et la prévention des blessures ? - Edouard, P.; Gremeaux, V.; Degache, F.; Gasq, D.; Calmels, P. (Movement & Sport Sciences - Science & Motricité, 2014)
The muscles of the rotator cuff appear to influence the throwing performance. Muscular adaptations induced by the repetition this throwing gesture and by the research of performance are considered as a risk factor for shoulder injury by a muscular "imbalance". Therefore, the exploration of the possible adaptations in muscle strength of internal rotators (IR) and external (ER), and the agonist/antagonist balance (ratio ER/IR) in response to the sports practice, is relevant in this context in order to better understand the physiological aspects of the overhead shoulder, as well as in a preventive approach. Isokinetic muscle strength evaluation currently appears the most appropriate technique to achieve it. Despite methodological limits related to the small sample sizes, the protocols used and the specific populations studied, many studies on overhead sports reported an adaptation of the rotator cuff strength, with an increase of IR strength of the dominant side, but it does not seem to co-exist real agonist/antagonist muscle "imbalance" with decreased of the ratio ER/IR. Thus, at the population level, overhead sports do not seem to induce a muscle imbalance that can be implicated as a risk factor predisposing to the shoulder injuries. However, at the individual level, the presence of muscle imbalance must be taken into consideration and it would be appropriate to identify and adapt the physical preparation, although scientific evidence is still modest.